Dry/wet sliding activation wear of pure Al / R. M. Nasir...[et al.] - Nasir, R. M.; B.T., Ting,; Saad, A. Y.; S., Mridha (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
An experimental work to study the wear behavior of pure Aluminium (Al) block was conducted against steel counter surface in Pin-on-Disc (POD) and the aluminium ball using four ball testing (4BT) method on dry/wet sliding wear technique at room temperature. Wear test conditions of 10-50 N load with sliding speed of 20-100 rpm was used to assess the friction coefficient, wear rate and the severance of wear mechanism on the damage surface. Due to the friction from the third body abrasive and protruded Al surfaces showcased mild wear with a steady state coefficient friction ranging from 0.0019-0.0043 for dry sliding and on wet condition ranging from 0.12-0.23 in vegetable oil (with average scar area of 8.0752 mm2) and from 0.058-0.085 for mineral oil used (with average scar area of 17.1549 mm2). Stress generation of the uncoated sample allowed the abraded plastic deformation to be classified as severe wear.